SHARIA ECONOMIC LAW REVIEW ON ZAKAT INSTITUTION AUDITS BY PUBLIC ACCOUNTANTS - Mari Kristanto, Prima (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2024)
The obligation to pay zakat for Muslims is a commitment to piety to Allah SWT and social and economic responsibility to fellow human beings. The role of government and society in optimizing the potential of zakat in Indonesia is marked by the presence of zakat management organizations (OPZ) in the form of amil zakat agencies and institutions. Currently, the government and society have paid high attention to zakat management institutions. Optimal management of zakat from both parties is supported by the stipulation of obligatory rules for zakat management institutions to prepare financial reports which are then audited by the Public Accounting Firm and the Ministry of Religion. The purpose of this research is to describe the implementation of sharia accounting and auditing at the Amil Zakat Ummul Quro Jombang Institute. The research method uses a descriptive qualitative approach. The collection of data used is interview, observation, and documentation. The results of the study state that the financial statements of the Amil Zakat Ummul Quro Institute have been presented by Statement of Financial Accounting Standards (PSAK) 109. The financial statements for 2021 have been audited by the Erfan and Rakhmawan Public Accounting Firm, audit activities are in line with sharia economic law. Sharia audit by the Regional Office of the Ministry of Religion of East Java Province in assessing financial transparency got a score of 32 out of a maximum score of 40.